2022
DOI: 10.3390/antiox11050809
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Water Supplemented with Acidifiers Improves the Growth Performance of Weaned Pigs and Potentially Regulates Antioxidant Capacity, Immunity, and Gastrointestinal Microbiota Diversity

Abstract: This study evaluated the potential effects of adding acidifiers to the drinking water on the growth performance, complete blood count, antioxidant indicators, and diversity of gastrointestinal microbiota for weaned pigs. A total of 400 weaned pigs were randomly divided into four treatments. Pigs were fed the same basal diet and given either water (no acidifier was added, control) or water plus blends of different formulas of acidifiers (acidifier A1, A2, or A3) for 35 days. On d 18 and 35 of the experimental p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 78 publications
(85 reference statements)
3
13
0
Order By: Relevance
“…Acidifiers, as vital feed additives in newly weaned piglets, play a critical role in the improvement of growth performance and the intestinal microbiota in pigs [ 30 ]. Our previous study found that supplementing a type of acidifier called Jinlisuan in drinking water increased the antioxidant capacity and immunity of weaned pigs [ 15 ]. However, its potential protective effects on intestinal epithelial cells and underlying molecular mechanism are not clear, especially after intestinal epithelial cells suffer from oxidative stress and present an inflammatory response [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acidifiers, as vital feed additives in newly weaned piglets, play a critical role in the improvement of growth performance and the intestinal microbiota in pigs [ 30 ]. Our previous study found that supplementing a type of acidifier called Jinlisuan in drinking water increased the antioxidant capacity and immunity of weaned pigs [ 15 ]. However, its potential protective effects on intestinal epithelial cells and underlying molecular mechanism are not clear, especially after intestinal epithelial cells suffer from oxidative stress and present an inflammatory response [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used the culture medium to dilute the liquid acidifier to analyze the optimal dosage in vitro. In the previous animal experiment, the purpose of diluting the acidifier was also achieved by adding liquid acidifier to drinking water [ 15 ]. Therefore, the effectiveness of an acidifier is determined by the dilution ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few acidifiers can form complexes with minerals such as calcium (Ca 2+ ) and zinc (Zn 2+ ) cations that will reduce their absorption in the digestive tract. Acidifiers have been generally recognized as safe (GRAS) agents since 1972 and have been used in poultry diets and drinking water for decades with positive responses on growth performance [ 95 , 96 , 97 ]. The feed acidifiers market is estimated to grow from US$2.7 billion in 2018 to US$3.5 billion by 2023 [ 98 ].…”
Section: Alternatives To Antibiotics As Growth Promotersmentioning
confidence: 99%
“…They concluded that melatonin supplementation during gestation could improve maternal–placental–fetal redox status and reproductive performance by ameliorating placental antioxidant status, inflammatory response and mitochondrial dysfunction. The work from Xu et al focused on the potential effects of adding acidifiers to drinking water [ 3 ]. The results showed that supplementing drinking water with an acidifier has potential as an antioxidant, which was reflected in improvements in growth performance, immunity, antioxidant capacity and intestinal flora.…”
mentioning
confidence: 99%